Resources - a league of extraordinary women [engineering profession]. - Patel-Predd, P. (IEEE spectrum)
This paper describes a new program in the US that is designed to attract young women to engineering. Dubbed the Extraordinary Women Engineers Project, the program is driven by a nationwide coalition of professional engineering societies as well as universities and technology companies. The program aims to make the general public, especially girls, aware of the importance of engineering in everyday life. Its plans include the release of a book and a television documentary on women in engineering and the airing of radio shows and developing resources for guidance counselors, teachers, and parents.